A comparative study of loRaWAN, sigFox, and NB-IoT for smart water grid - Lalle, Yandja (2020)
Low Power Wide Area Networks (LPWAN) are becoming the powerful communication technologies of the IoT of tomorrow. LoRaWAN, SigFox, and NB-IoT are the three competing LPWAN technologies. On the other hand, Smart Water Grid (SWG) is an emerging paradigm that promises to overcome issues such as pipes leaks encountered by current water infrastructure by deploying smart devices into the water infrastructure for monitoring purposes. This paper firstly explores the physical and communication features of the above LPWAN technologies and provides a comprehensive comparison between them as well as their suitability for the Smart Water Grid (SWG) use case. The important aspect of SWG is to connect devices such as smart water meters and other tiny devices like sensors installed into the water pipelines for the system monitoring purpose. We consider Advanced Metering Infrastructure (AMI) also called Smart Water Metering when dealing with the water grid, which is the main application of SWG and we study the scalability of LoRaWAN, NB-IoT, and SigFox in such application. Under NS3, the simulation results show that NB-IoT provides the best scalability compared to LoRaWAN and SigFox and thus is able to support a huge number of devices with a low packet error rate.